Translating Ioudaios concepts in multifaceted contexts : an intertextual approach to the rhetoric of 1 Corinthians 15 - Owiredu, Kennedy Kwame (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.